Knowledge, attitude and practice survey towards COVID‐19 vaccination: A mediation analysis. (28th February 2022) - Sengupta, Mitali; Dutta, Smita; Roy, Arijit; Chakrabarti, Satyajit; Mukhopadhyay, Indraneel
Abstract: Background and Aim: The COVID‐19 pandemic has significantly impacted human lives across the world. In a country like India, with the second highest population in the world, impact of COVID‐19 has been diverse and multidimensional. Under such circumstances, vaccination against COVID‐19 infection is claimed to be one of the major solutions to contain the pandemic. Understanding of Knowledge, Attitude and Practice (KAP) measures are essential prerequisites to design suitable intervention programs. This paper examines the different KAP factors in Indians towards their decision of vaccine uptake. Method: An online questionnaire was administered to Indian respondents. (Pilot study: n = 100, Main study: n = 221) to assess their existing knowledge on COVID‐19 infections and vaccination, attitude and intentions towards COVID‐19 vaccines and their decision towards COVID‐19 vaccine uptake. Result: The findings highlighted that existing knowledge on COVID‐19 infections and vaccination directly impacted their attitude and intention towards vaccination. The attitude and intention towards COVID‐19 vaccines directly impacted their practice of undergoing COVID‐19 vaccination. Further, there was a statistically significant and considerably large indirect effect of existing knowledge on COVID‐19 infections and vaccination on the practice of undergoing COVID‐19 vaccination through attitude and intention towards the vaccine. There was no direct effect of Knowledge (existing knowledge on COVID‐19 infections and vaccination) on Practice (decision to undergo COVID‐19 vaccination). Therefore, Attitude and intention towards COVID‐19 vaccine is the primary mediator between Knowledge (existing knowledge on COVID‐19 infections and vaccination) and Practice (decision to undergo COVID‐19 vaccination). Conclusion: Participants decision towards COVID‐19 vaccination decisions are strongly related to their attitude and intentions that confirms the strong role of attitude towards success of COVID‐19 vaccination programme. Therefore, 'person‐centric' attitude based positive intervention strategies that links their prior knowledge on COVID‐19 infections and vaccination must be designed for greater vaccine acceptance amongst Indians. Highlights: Knowledge is the key to successful COVID‐19 vaccination drive which is deemed to be essential for ending the global pandemic. Knowledge positively affects attitude and attitude positively impacts COVID‐19 vaccine uptake decision. Attitude completely mediates the relationship between respondent's knowledge and their decision of COVID‐19 vaccination. Specific awareness campaigns towards COVID‐19 vaccination aimed at attitude restructuring are needed.